2021
DOI: 10.3390/jfmk6020040
|View full text |Cite
|
Sign up to set email alerts
|

Biological Determinants of Track and Field Throwing Performance

Abstract: Track and field throwing performance is determined by a number of biomechanical and biological factors which are affected by long-term training. Although much of the research has focused on the role of biomechanical factors on track and field throwing performance, only a small body of scientific literature has focused on the connection of biological factors with competitive track and field throwing performance. The aim of this review was to accumulate and present the current literature connecting the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 60 publications
0
17
0
1
Order By: Relevance
“…Increasing muscle mass is of high importance in (elite) sports (Del Vecchio et al, 2019;Kordi et al, 2020;Zaras et al, 2021), prevention -especially in age-related diseases such as sarcopenia (English and Paddon-Jones, 2010;Lopes et al, 2019;Vikberg et al, 2019) -and rehabilitation of orthopedic indications (Wada et al, 2020). Consequently, several training methods aim to improve muscle mass which is usually measured via muscle thickness (MT) or muscle cross-sectional area (MCSA) (Schoenfeld et al, 2016;Simpson et al, 2017;Wackerhage et al, 2019;May et al, 2021), also in rehabilitative settings (Guthrie et al, 2012;Larivière et al, 2019;Padulo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing muscle mass is of high importance in (elite) sports (Del Vecchio et al, 2019;Kordi et al, 2020;Zaras et al, 2021), prevention -especially in age-related diseases such as sarcopenia (English and Paddon-Jones, 2010;Lopes et al, 2019;Vikberg et al, 2019) -and rehabilitation of orthopedic indications (Wada et al, 2020). Consequently, several training methods aim to improve muscle mass which is usually measured via muscle thickness (MT) or muscle cross-sectional area (MCSA) (Schoenfeld et al, 2016;Simpson et al, 2017;Wackerhage et al, 2019;May et al, 2021), also in rehabilitative settings (Guthrie et al, 2012;Larivière et al, 2019;Padulo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Higher RFD, strength, and lean mass have been frequently reported as crucial determinant parameters of track and field throwing performance (2,21,28,37,(39)(40)(41)(42). In addition, training-induced increases in the above parameters have also been linked with increases in throwing performances (2,21,28,37,(39)(40)(41)(42). The results of this study are further supported by previous reports about the role of lower-body RFD, maximum strength, and lean mass on competitive track and field throwing performance in well-trained throwers (2,33,34,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis showed that the linear combination of the percentage change in RFD 150ms , 1RM in snatch and back squat, and lean mass could predict approximately the 80% of competitive track and field throwing performance increase after both CPX and CPD training. Higher RFD, strength, and lean mass have been frequently reported as crucial determinant parameters of track and field throwing performance (2,21,28,37,(39)(40)(41)(42). In addition, training-induced increases in the above parameters have also been linked with increases in throwing performances (2,21,28,37,(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…A few authors have identified some of the key factors influencing force magnitude in the thrower. Among these, lean mass, muscle fiber type and architectural characteristics of the muscles appear to predominantly contribute (Zaras et al, 2021 ). Mass significantly influences the amount of force produced because heavier throwers usually also have a greater volume of muscle allowing for an enhanced capacity to apply forces on the hammer cable (Billeter et al, 2003 ; Gutierrez-Davila and Rojas-Ruiz, 2005 ; Okamoto et al, 2007 ; Singh et al, 2011 ).…”
Section: Forces Involved In the Throwmentioning
confidence: 99%